Analyzing the Influence of Digital Marketing Strategies on Business Performance in the Beauty Industry: A Comprehensive Analysis of Social Media Engagement and Influencer Collaborations - Zakwan Fadil Bakri (Journal on Economics, Management and Business Technology, 2023)
This research investigates the impact of digital marketing strategies on business performance within the beauty industry. The study aims to analyze the correlation between various digital strategies social media engagement, influencer collaborations, personalized content, data-driven approaches, and omnichannel integration and their influence on key performance indicators such as sales growth, consumer trust, loyalty, and marketing ROI. A mixed-methods approach was employed, incorporating qualitative methods like interviews and focus groups with industry experts and consumers, alongside quantitative surveys distributed among beauty brands. Thematic analysis was conducted on qualitative data, while statistical analysis, including correlation and regression, was applied to quantitative data. Findings reveal a significant positive correlation between robust social media engagement metrics and increased sales growth, emphasizing the pivotal role of social platforms in revenue generation. Additionally, influencer collaborations emerged as influential drivers of consumer trust and purchase intent. Personalized content was found to foster higher customer loyalty, while data-driven strategies significantly improved marketing ROI. Effective omnichannel integration positively impacted overall customer satisfaction and brand perception. Implications for businesses in the beauty industry include the need to prioritize engaging content creation, authentic influencer partnerships, personalized marketing approaches, data-driven decision-making, and seamless omnichannel experiences. Addressing challenges such as digital saturation, privacy concerns, and platform dynamics while leveraging strengths in reach, targeting, and engagement will be crucial for sustained growth and competitiveness.